Helperconnect / Leviana Andrew ... [et al.] - Andrew, Leviana; Mat Yusof, Marlita; Wan Ibrahim, Wan Muhd Faez; Hassan, Siti Salwa; Haris, Nurfazlina (Universiti Teknologi MARA, Kedah, 2024)
In an increasingly digital world, accessibility and convenience are critical for individuals with disabilities and older citizens. Our proposed platform addresses these challenges by connecting users with reliable helpers for daily errands and companionship. Through a user-friendly interface available on web and mobile devices, the platform ensures dependable service with vetted helpers. By utilizing a robust matching algorithm, users can find assistance tailored to their specific needs. Our marketing strategies include digital campaigns, partnerships with advocacy groups, and referral programs. The service offers a commission-based fee structure for sustainability, combining essential errand running with genuine companionship to enhance users' overall quality of life. This innovative approach promises to significantly improve accessibility and social interaction for those who need it most.